100% recycled high-modulus asphalt concrete mixture design and validation using vehicle simulator. (10th November 2020) - Zaumanis, M.; Arraigada, M.; Poulikakos, L.D.
Graphical abstract: Highlights: RAP properties are well matched for use in high-modulus asphalt mixtures. Laboratory performance of 100% RAP HMAC is close to reference mix. Traffic load simulator reveals insufficient cracking resistance of 100% RAP mixes. Crack propagation testing is recommended for design of high content RAP mixtures. Higher binder content is required in 100% RAP mixes compared to reference. Abstract: High modulus asphalt concrete (HMAC) mixtures are designed for high rutting resistance, high modulus and excellent fatigue performance. This is achieved through the use of high content of hard bitumen, low air void content, and use of performance-based testing for mixture design. Such approach is presumably well-matched for application of Reclaimed Asphalt Pavement (RAP): the RAP binder is hard because of aging, RAP mixtures inherently have low air voids and performance-based mix design is recommended to increase the degree of reliability when using high RAP mixtures. Here we present a study focused on designing and validating performance of HMAC from 100% RAP. Through multiple design iterations we found that it was not possible to fully fulfill the fatigue, modulus and rutting requirements for either of the recycled HMAC mixture types (C1 or C2) although the performance of one of the 100% RAP mixtures came close to the HMAC design requirements. Nevertheless, validating of the best-performing 100% RAP HMAC slabs using vehicle load simulator demonstrated that the recycled HMAC is significantly less resistant towards crack propagation compared to a conventional HMAC. This highlights the importance of testing cracking resistance for high RAP mixtures.